Simplifying
-1x + -7 = 5x + -11 + -7x
Reorder the terms:
-7 + -1x = 5x + -11 + -7x
Reorder the terms:
-7 + -1x = -11 + 5x + -7x
Combine like terms: 5x + -7x = -2x
-7 + -1x = -11 + -2x
Solving
-7 + -1x = -11 + -2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2x' to each side of the equation.
-7 + -1x + 2x = -11 + -2x + 2x
Combine like terms: -1x + 2x = 1x
-7 + 1x = -11 + -2x + 2x
Combine like terms: -2x + 2x = 0
-7 + 1x = -11 + 0
-7 + 1x = -11
Add '7' to each side of the equation.
-7 + 7 + 1x = -11 + 7
Combine like terms: -7 + 7 = 0
0 + 1x = -11 + 7
1x = -11 + 7
Combine like terms: -11 + 7 = -4
1x = -4
Divide each side by '1'.
x = -4
Simplifying
x = -4